Transplant-Associated Thrombotic Microangiopathy in Pediatric Hematopoietic Cell Transplant Recipients: A Practical Approach to Diagnosis and Management - Dvorak, Christopher C.; Higham, Christine; Shimano, Kristin A. (Frontiers in Pediatrics, 2019)
Transplant-associated thrombotic microangiopathy (TA-TMA) is an endothelial damage syndrome that is increasingly identified as a complication of both autologous and allogeneic hematopoietic cell transplantation (HCT) in children. If not promptly diagnosed and treated, TA-TMA can lead to significant morbidity (e.g., permanent renal injury) or mortality. However, as the recognition of the early stages of TA-TMA may be difficult, we propose a TA-TMA “triad” of hypertension, thrombocytopenia (or platelet transfusion refractoriness), and elevated lactate dehydrogenase (LDH). While not diagnostic, this triad should prompt further evaluation for TA-TMA. There is increased understanding of the risk factors for the development of TA-TMA, including those which are inherent (e.g., race, genetics), transplant approach-related (e.g., second HCT, use of HLA-mismatched donors), and related to post-transplant events (e.g., receipt of calcineurin inhibitors, development of graft-vs. -host-disease, or certain infections). This understanding should lead to enhanced screening for TA-TMA signs and symptoms in high-risk patients. The pathophysiology of TA-TMA is complex, resulting from a cycle of activation of endothelial cells to produce a pro-coagulant state, along with activation of antigen-presenting cells and lymphocytes, as well as activation of the complement cascade and microthrombi formation. This has led to the formulation of a “Three-Hit Hypothesis” in which patients with either an underlying predisposition to complement activation or pre-existing endothelial injury (Hit 1) undergo a toxic conditioning regimen causing endothelial injury (Hit 2), and then additional insults are triggered by medications, alloreactivity, infections, and/or antibodies (Hit 3). Understanding this cycle of injury permits the development of a specific TA-TMA treatment algorithm designed to treat both the triggers and the drivers of the endothelial injury. Finally, several intriguing approaches to TA-TMA prophylaxis have been identified. Future work on the development of a single diagnostic test with high specificity and sensitivity, and the development of a robust risk-scoring system, will further improve the management of this serious post-transplant complication.